The ratio of absolute lymphocyte count at interim of therapy to absolute lymphocyte count at diagnosis predicts survival in childhood B-lineage acute lymphoblastic leukemia. Issue 2 (February 2015) - Cheng, Yuping; Luo, Zebin; Yang, Shilong; Jia, Ming; Zhao, Haizhao; Xu, Weiqun; Tang, Yongmin
Highlights We analyzed the impact of ALC-22/ALC-0 ratio on survival in 119 pediatric B-ALL patients. ALC-22/ALC-0 ratio <10% was associated with inferior 5-year OS and EFS. ALC-22/ALC-0 ratio reflected the host immunity and bone marrow recovery. ALC was mainly associated with CD3+ T cells. ALC-22/ALC-0 ratio is a novel, simple and effective biomarker to predict survival.